Interés y motivación de los estudiantes de la carrera de comunicación en programas de capacitación, año 2023 - Vergara Parra, Andrea Carolina (Machala: Universidad Técnica de Machala, 2023)
The objectives of the research is to investigate the interest and motivations on the academic training programs of the students of the Social Communication career of the city of Machala. In order to find out if they would take courses during their time as a student, at what stage of their career would they prefer to take them, what do they think would be their advantages and disadvantages of accessing a seminar or training, the time they would dedicate to these extra studies, their preferences in subjects, what type of professional would be their preference, the duration of these or why they would not take a course, who influence their decision making. This is how we worked with a sample of the population of the students of the career, from the fourth to the eighth semester. The research had a quantitative and qualitative approach, surveys were applied where the interest of the students in taking training courses was known, it can be seen that according to the students there is a shortage in terms of topics of interest, which have preferential days such as Mondays and Tuesday to attend some type of academic activity, the multiple realities for which they would or would not take a course such as monetary or time were analyzed, continuing to educate themselves is important for students, which is why the vast majority have seen the continue to educate themselves, let them know that time in the classroom is limited and does not allow them to explore all the topics they believe are necessary for their life in the professional field.
Los objetivos de la investigación es indagar el interés y motivaciones sobre los programas de capacitación académica, de los estudiantes de la carrera de Comunicación Social de la ciudad de Machala. Con la finalidad de conocer si tomarían cursos durante su tiempo como estudiante, en qué etapa de su carrera les parecería preferencial realizarlas, cuales creen que serían sus ventajas y desventajas de acceder a algún seminario o capacitación, el tiempo que dedicarían a estos estudios extra, sus preferencias en temas, que tipo de profesional seria de su preferencia, la duración de estos o porque no tomarían algún curso, quienes influyen en su toma de decisiones. Así se trabajó con una muestra de la población de los estudiantes de la carrera, desde cuarto a octavo semestre. La investigación tuvo enfoque cuantitativo y cualitativo, se aplicaron encuestas donde se conoció el interés de los estudiantes por tomar cursos de capacitación, se deja entrever que según los estudiantes existen un faltante en cuanto a temas de interés, que tienen días preferenciales como los lunes y martes para asistir a algún tipo de actividad académica, se analizó las múltiples realidades por las cuales tomarían o no un curso como monetario o tiempo, el seguir educándose es importante para los alumnos es por esto que en su gran mayoría han visto como una oportunidad el seguirse instruyendo, dejan conocer que el tiempo en las aulas es limitado y no deja explorar todos los temas que creen necesario para su vida en el campo profesional.
Keywords: FORMACION; CAPACITACION; NECESIDAD; COMUNICACION